Prosaic Poetry and Pneumatic Craving in Southey’s Curse of Kehama - Colman, Adam (Romanticism on the Net)

(untitled) (Université de Montréal, 2017)
Among those affiliated with Thomas Beddoes’s Pneumatic Institution in Bristol, there were a number who poetically emphasized the hopeful attributes of scientific pursuit. Coleridge did so; Humphry Davy did in his poetry, too; Robert Southey had early on asserted the connection between scientific study and hope. Southey, however, would remark that he had undergone especially volatile responses to nitrous oxide. His sense of adventures through a material world would, in the years following his time spent at the Pneumatic Institution, become conflicted. He would, in particular, register pneumatically inflected hopes in less idealistic terms than Coleridge or Davy. Instead, Southey’s poetry has passages containing descriptions of pneumatic desires in terms of anguished bodily craving. This essay considers how Southey’s Curse of Kehama, published in 1810, locates an especially vexed sense of bodily craving in the kind of thinking about matter and air associated with the Pneumatic Institution. I examine how such physically wrenching desire relates to the form of Southey’s poem, wherein certain poetic rhythms of anticipation—iterations suggesting others still to come—operate within a more prosaic realm of conflicted, irregularly interconnected, material immanence.